2019
DOI: 10.1177/0021998319883335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of machining damage generated during trimming of CFRP composite on the compressive strength

Abstract: Machining of composite materials is a challenging task due to the heterogeneity and anisotropy of composite structures. The induced defects reduce integrity of the machined surface as well as the loading capacity of the composite structure in service. Therefore, it is necessary to quantify the damage induced during trimming and correlate the quality of the machined surface to mechanical properties. The correlation of the surface roughness criteria, widely used in literature, to the mechanical behavior raise se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This is vitally important as the defect type and size have been directly linked to mechanical performance. 9,[23][24][25][26] By using the EF method, a novel metric which accounts for machining induced damage of CFRP edge trimming has been generated. The novel metric is able to provide a value for total damage area compared to a theoretically straight cut.…”
Section: Discussionmentioning
confidence: 99%
“…This is vitally important as the defect type and size have been directly linked to mechanical performance. 9,[23][24][25][26] By using the EF method, a novel metric which accounts for machining induced damage of CFRP edge trimming has been generated. The novel metric is able to provide a value for total damage area compared to a theoretically straight cut.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,20 A machined multidirectional composite surface has been shown to have a non-homogeneous surface: this has been shown in the literature using various methods, including computed tomography (CT), scanning electron microscopy (SEM) and optical focus variation measurement techniques. 11,12,16,21 Other researchers have used advanced techniques to assess sub surface damage including terahertz imaging and epiflourescent microscopy. 22,23 Wang et al 24 have used a new image subtraction method to quantify the extent of delaminated fibres on an edge trimmed edge using an image subtraction method.…”
Section: Review Of State-of-the-art Measurement Methods and Statisticmentioning
confidence: 99%
“…1 Previous studies have indicated that surface defects and machining induced surface roughness can affect the mechanical performance of composite material. [12][13][14] It has been shown by Haddad et al, 15 that the cutting speed will have a significant effect on surface roughness. Further research indicates that surface roughness will play a role in reducing inter-laminar shear strength in IMS/977-2 composite samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the most studied factors to evaluate delamination produced after milling are cutting parameters, fiber orientation angle and cutting tool characteristics (material, teeth number, etc.) [ 4 , 5 , 6 , 7 , 8 ]. Cutting speed and feed are mainly studied [ 9 , 10 , 11 , 12 ], but only a few authors also include depth of cut [ 13 ] since most of them think that its influence on delamination is not as relevant as cutting speed and feed.…”
Section: Introductionmentioning
confidence: 99%